Prediction of Dynamic Milling Stability considering Time Variation of Deflection and Dynamic Characteristics in Thin-Walled Component Milling Process - Li Zhang; Weiguo Gao; Dawei Zhang; Yanling Tian (Shock and Vibration)
The milling stability of thin-walled component is an important problem in the aviation manufacturing industry. The milling stability is influenced by both deflection characteristic and dynamic characteristic of workpiece. Moreover, in the material removal, the deflection and dynamic characteristics of workpiece are time-variant on the change of machining positions. Thus, the milling stability is also time-variant. In order to investigate the time variation of deflection and dynamic characteristics of workpiece, a new computational model was established in this paper. Based on the influences of the deflection and the dynamic characteristics of workpiece, a new stability lobes diagram which can show different stability domains and chatter domains in different process positions was obtained. Experimental testing has been conducted to validate the established new model.